(untitled) (Journal of the College of Education for Women, 2018)
The research aims to focus on the human rights guarantees as they are subjected to continuous violations due to changes, wars and conflicts between nations and people, especially in the Arab world and the third world due to political, social, economic and environmental conditions and the failure of democratic tracks under the current reality. Keyword: Human rights, Reality, Ambition.